Western media coverage of Ukraine Vs Gaza Wars: Bias or Professionalism ? - MERAGHNI, Ahmed Amine; GOURZI, Mohammed Samir (University of Eloued جامعة الوادي, 2024)
The present study compares the coverage of the wars in Gaza and Ukraine by Western media outlets in order to determine whether such coverage was unprofessional or biased towards one conflict. Accordingly, a mixed-methods approach, consisting of framing analysis and quantitative methods, was used to show how the media portrayed these two conflicts. A total of 49 news articles and 14 videos were collected from four media outlets: BBC News, CNN, Fox News, and New York Time, and quantitatively analyzed using a coding scheme that consists of 16 frames categorized under three main predefined news frames, namely generic, diagnoses, and prognoses. The obtained finding demonstrate that the four media outlets were more concerned with explaining the causality of the war in Ukraine and Gaza (61.25% and 55.5% respectively for generic frames) than highlighting the wider social and economic backgrounds of the conflicts (diagnostic: 42.5% and 38.75% respectively), or suggesting solutions for the two crises (prognostic: 34.37%, 35.57% respectively) although bias was blatant in favor of Ukraine. While media and people in the west continued to hold Gaza, particularly Hamas, responsible for the crisis, they portrayed Ukraine as a victim and in a constant need of assistance even though it is receiving aid from all over the world. This question the level of professionalism of western media outlets in covering wars that fall beyond their geopolitical interest. This study helps enhance readers’ knowledge of the many vantage points that various media outlets adopt when covering the same event. الدراسة الحالية تقارن تغطية الحروب في غزة وأوكرانيا من قبل وسائل الإعلام الغربية لتحديد ما إذا كانت مثل هذه التغطية غير مهنية ومتحيزة لصالح إحدى النزاعات. تم استخدام نهج مختلط يجمع بين تحليل التأطير والنهج الكمي لإظهار كيفية تصوير الإعلام للنزاعين بطريقة متحيزة أو مهنية. تم جمع مجموعة من الأخبار والفيديوهات تتألف من 49 مقالة و 14 فيديوًا من أربعة وسائل إعلام: BBC News، CNN، Fox News، و New York Times. تم إجراء تحليل كمي على الأخبار والفيديوهات المختارة باستخدام مخطط ترميز يتألف من ثلاثة إطارات رئيسية: الإطار العام، التشخيصات، والتوقعات، تليها إطارات فرعية تقارن النزاعين الاثنين بناءً على هذه الإطارات. أظهرت النتائج أن الوسائل الأربعة للإعلام قدمت تقريرًا متحيزًا حول الوضع في أوكرانيا، حيث قدمت أوكرانيا للمجتمع العالمي كبلد يحتاج إلى مساعدة على الرغم من أنها تتلقى مساعدات من جميع أنحاء العالم. بينما قدمت غزة جانب قصتها، واصلت وسائل الإعلام والناس في الغرب تحميل غزة مسؤولية الأزمة. تساعد هذه الدراسة في تعزيز معرفة القراء بالعديد من وجهات النظر المختلفة التي تتبناها وسائل الإعلام المختلفة عند تغطية نفس الحدث.
Literature and Civilization
Keywords: framing analysis; Gaza crisis; media coverage; Ukraine crisis; أزمة أوكرانيا، أزمة غزة، التغطية الإعلامية، تحليل التأطير